Chaotic Lorenz Synchronization Circuit Design for Secure Communication - Deniz, Halil Ibrahim; Taskiran, Zehra Gulru Cam; Sedef, Herman (IEEE, 2018)
Chaos which is a complex, nonlinear and deterministic behavior have many fields of applications. This theory, which Lorenz describes with a simple mathematical model, has become a very important issue in the field of nonlinear circuits and systems. The discovery of the existence of chaos has opened up many different developments. One of these developments is to recognize that secure communication systems can be implemented with these systems by deriving from the sensitivity of chaotic systems to initial conditions. In this paper, a circuit based on Lorenz equations is synchronized for secure communication. The Lorenz circuit is adapted to two different synchronization methods. The synchronization circuits are analyzed mathematically in MATLAB, and the simulated in PSPICE. A secure communication system has been tested for both methods. The system results are compared.
Keywords: chaotic circuit; chaos; Lorenz equations; non-linear analysis; synchronization; LAG SYNCHRONIZATION; SYSTEMS; Automation & Control Systems; Computer Science; Engineering